2013
DOI: 10.1073/pnas.1301577110
|View full text |Cite
|
Sign up to set email alerts
|

Latency of Epstein–Barr virus is disrupted by gain-of-function mutant cellular AP-1 proteins that preferentially bind methylated DNA

Abstract: ZEBReplication Activator (ZEBRA), a viral basic zipper protein that initiates the Epstein–Barr viral lytic cycle, binds to DNA and activates transcription through heptamer ZEBRA response elements (ZREs) related to AP-1 sites. A component of the biologic action of ZEBRA is attributable to binding methylated CpGs in ZREs present in the promoters of viral lytic cycle genes. Residue S186 of ZEBRA, Z(S186), which is absolutely required for disruption of latency, participates in the recognition of methylated DNA. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…While such methylated bases inhibit most transcription factors from activating gene expression, the Z protein actually has a preference for the methylated forms of many viral and cellular promoters [25,73,8690]. Z binding to methylated ZREs requires serine residue 186 located within its DNA-binding domain [87,91]; the equivalent position in c-Jun and c-fos contains an alanine residue. Conversion of these alanines to serines enables these latter proteins to also activate methylated Rp [91].…”
Section: Role Of Genome Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…While such methylated bases inhibit most transcription factors from activating gene expression, the Z protein actually has a preference for the methylated forms of many viral and cellular promoters [25,73,8690]. Z binding to methylated ZREs requires serine residue 186 located within its DNA-binding domain [87,91]; the equivalent position in c-Jun and c-fos contains an alanine residue. Conversion of these alanines to serines enables these latter proteins to also activate methylated Rp [91].…”
Section: Role Of Genome Methylationmentioning
confidence: 99%
“…Z binding to methylated ZREs requires serine residue 186 located within its DNA-binding domain [87,91]; the equivalent position in c-Jun and c-fos contains an alanine residue. Conversion of these alanines to serines enables these latter proteins to also activate methylated Rp [91]. Z’s unique ability to activate methylated promoters helps to ensure rapid EBV reactivation following Z synthesis, despite the EBV genome being methylated in most latently infected cells (Fig.…”
Section: Role Of Genome Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13). Z (also known as EB1, ZEBRA, and Zta) is a bZip protein homologous to AP-1 and binds to AP-1-like sites (Z-responsive elements, ZREs) that often contain CpG motifs (11,(13)(14)(15). Once established, EBV genome methylation is maintained during latent viral genome replication (licensed and mediated by host cell replication machinery) via the enzymatic activity of DNA methyltransferases (1,2).…”
mentioning
confidence: 99%
“…It has been demonstrated that a methylated EBV genome is essential for viral lytic reproduction (51,53,72), as the immediate-early protein Zta preferentially binds to methylated viral promoters (54,(73)(74)(75). In 293T cells stably infected with an EBV genome, high occupancies of Zta were observed in methylated promoters of BALF2, BMRF1, Rta, and BHLF1, whereas these bindings were disrupted once the EBV genome is hypomethylated (54).…”
Section: Discussionmentioning
confidence: 97%